The COVID-19 pandemic and overconfidence bias: The case of cyclical and defensive sectors - Md Qamar Azam; Nazia Iqbal Hashmi; Iqbal Thonse Hawaldar; Md Shabbir Alam; Mirza Allim Baig (Risks, 2022)
This research paper analyses the impact of COVID-19 to investigate the overconfidence bias in 12 cyclical and defensive sectors in pre- and during COVID-19 periods using daily data from 1 January 2015 to 31 December 2020. The results of VAR show that in the pre COVID-19 phase overconfidence bias is more prevalent in all the cyclical sectors; in particular, MEDIA, METAL and REALTY have highly significant coefficients . In the defensive sectors, the VAR outcomes are not as strong as we expected, except for SERVICES. During the COVID-19 period, the investor shifted their focus to COVID-19-related opportunities, leading to a surge in the IT and PHARMA sectors. In both phases, METAL, MEDIA and REALTY exhibit overconfidence-driven stock trading behaviour. ENERGY is the only sector in both the phases that does not witness overconfidence bias.
Keywords: 330; COVID-19; overconfidence bias; sectors; VAR